Application of Bayes Method to Predicting Vertigo Disease - Syaiful Ikhram Lubis; Lubis, Imran; Suci Ramadani (Journal of Artificial Intelligence and Engineering Applications (JAIEA), 2024)
Health is very important in life. However, sometimes awareness of a healthy lifestyle and regular diet is still neglected. Many diseases and symptoms arise due to irregular lifestyle and diet, one of which is vertigo. Vertigo is a different type of headache from regular headaches and migraines. It involves a sensation of movement or a feeling of motion of the body or surrounding environment, caused by a disturbance of the body's balance. Symptoms include a feeling of spinning, a swaying sensation, or a spinning environment, often accompanied by nausea, vomiting, cold sweat, and the urge to lie down to feel better. From the Bayes method calculation process in this study, it can be seen that the patient suffers from Vertigo disease, namely Vertigo Central (P02) with a value of 0, 7212 or 72.12%.